Aplicación de la ley 1696 de 2013 frente a las infracciones tipo F en el departamento del Huila para el 2018 y 2019 (2022)
Given the importance of regulating the driving of a motor vehicle under the influence of alcohol, which is directly associated with the increased risks generated by driving under the influence of alcohol, and in turn the serious danger to the rights and interests of the subjects interacting on public roads, law 1696 of D ecember 19, 2013 becomes a strategy to punish such behaviors; the following research project refers to the study of the "Errors in the application of the law 1696 of 2013 against type F infractions, in the department of Huila for 2018 and 2019" ; the metho dology proposed by the authors proposes a descriptive identify the factors that lead to the non-- transversal study of qualitative type in order to materialization of contraventions due to administrative type errors in a sample of 10 contraventional rulings. The results show the existence of type errors, incomplete documentation among others; it is concluded that the misdemeanor processes analyzed present administrative errors against the protocols defined by the National Institute of Forensic Medicine and Fo rensic Sciences (INMLCF)